Heparin, Heparin-like Molecules, and Heparin Mimetics in Breast Cancer: A Concise Review - Diego R. Gatica Portillo; Yishu Li; Navneet Goyal; Brian G. Rowan; Rami A. Al-Horani; Muralidharan Anbalagan (Biomolecules)
Heparin and heparan sulfate are essential in various biological processes relevant to cancer biology and pathology. Given the clinical importance of breast cancer, it is of high interest to seek more effective and safer treatment. The application of heparins (UFH, LMWH, ULMWH, fondaparinux) and heparin mimetics as potential treatments is particularly interesting. Their use led to promising results in various breast cancer models by exhibiting anti-angiogenic and anti-metastatic properties. This article concisely reviews studies involving heparins and mimetics in both in vitro and in vivo breast cancer settings. We highlight molecules, conjugates, delivery systems, and combinations involving heparin or its mimetics. We also survey several potential biological targets such as VEGF, FGF-2, TGFβ-1, PDGF-B, NPP-1, CXCL12-CXCR4 axis, and CCR7-CCL21 axis. Overall, heparins and their mimetics, conjugates, and combinations represent a powerful strategy to effectively and safely treat breast cancer, which is the most common cancer diagnosed in women worldwide and the fifth leading cause of cancer-related deaths worldwide.